Librarians' Conceptions of Expertise: An Intersectional Exploration. Issue 1 (14th October 2022) - Hicks, Deborah; VanScoy, Amy; Julien, Heidi
ABSTRACT: This poster describes an interview study with librarians representing a broad range of demographics, career stages, and professional roles. The goal of the study is to explore librarians' perceptions of their own professional expertise, and to analyze those perceptions through an intersectional lens. Intersectionality refers to a theoretical perspective that posits that people's intersecting social identities (e.g., gender, race, age, etc.) relate to their experiences, particularly of marginalization, and to systems of oppression. An intersectional understanding of professional expertise as experienced by library workers can expose existing structures that serve to marginalize or stigmatize some forms of expertise, with a goal to establish more equitable and just information organizations.